2019
DOI: 10.2139/ssrn.3473702
|View full text |Cite
|
Sign up to set email alerts
|

On the Determinants of Pro-Environmental Behavior: A Literature Review and Guide for the Empirical Economist

Abstract: This paper provides a systematic review of current economic and psychological studies on the determinants of PEB published up to 2017. Our normative understanding and study of PEB can benefit from an integral review of these research traditions. Consequently, we identify various determinants of PEB that can be classified into four major types: • Socio-demographic factors (personal capabilities) • Attitudinal (psychological) factors • Habits • Contextual factors (individual, social and institutional) Our paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 126 publications
(215 reference statements)
6
61
1
6
Order By: Relevance
“…At the same time, the importance "of analyzing the impact of´moral´emotions (author´s note: e.g., contempt, anger, shame, guilt) on pro-environmental intentions in future studies" was indicated [13] (pp. [21][22].…”
Section: Determinants Of Pro-environmental and Sustainable Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, the importance "of analyzing the impact of´moral´emotions (author´s note: e.g., contempt, anger, shame, guilt) on pro-environmental intentions in future studies" was indicated [13] (pp. [21][22].…”
Section: Determinants Of Pro-environmental and Sustainable Behaviormentioning
confidence: 99%
“…Besides the predictors on a psychological level, as illustrated above, sociodemographic variables can also be important in predicting pro-environmental and sustainable behavior. Blankenberg and Alhusen [21] provided a systematic review (n = 158) showing a combined influence of psychological and sociodemographic variables, which underscores the importance of multivariate analysis of influencing constructs on different levels. Age displayed a U-shaped progression over lifespan [21] as well as U-shaped progression within adolescence with respect to sustainability consciousness [22,23].…”
Section: Determinants Of Pro-environmental and Sustainable Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Coertjens et al [23] see a reason for this finding in the measure of SES in PISA, as it is comprised of diverse subdomains of SES [20]. Therefore, the typical finding of SES as strong predictor for pro-environmental variables ( [71], for a review, see [65,72]) might be reduced due to the operationalization in PISA.…”
Section: Rq2: Correlates Of Environmental Awarenessmentioning
confidence: 99%